1994
DOI: 10.1139/x94-053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermediate silvicultural treatments on the distribution of within-stand growth

Abstract: The distribution of within-stand basal area growth following silvicultural treatments was investigated using a relative size–relative growth (RSG) function. The effects of thinning on the distribution of tree basal area, including changes in location or scale, can be incorporated into the estimation of the RSG function parameters. Additional stand growth due to fertilization can also be allocated to individual trees using the same RSG function, since the contribution of a tree's response to total stand treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 7 publications
5
12
1
Order By: Relevance
“…This is in accordance with the results of Pukkala et al (1998), that co-dominant and medium-sized Scots pine trees had the highest relative response to thinning. The result is also supported by the findings of Moore et al (1994) in Douglas fir, that large trees are relatively less affected by thinning than smaller trees. In contrast, Jonsson (1974) and Hynynen (1995) found that the relative thinning response within a Scots pine stand was the same irrespective of tree size.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is in accordance with the results of Pukkala et al (1998), that co-dominant and medium-sized Scots pine trees had the highest relative response to thinning. The result is also supported by the findings of Moore et al (1994) in Douglas fir, that large trees are relatively less affected by thinning than smaller trees. In contrast, Jonsson (1974) and Hynynen (1995) found that the relative thinning response within a Scots pine stand was the same irrespective of tree size.…”
Section: Discussionsupporting
confidence: 78%
“…Moore et al, 1994;Eriksson and Karlsson, 1997). The reason for the effect is obvious because smaller trees were removed in the thinnings, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our hypothesis and again consistent with previous findings that reported that small and medium-size trees have the highest relative response to thinning [56,57,59,60]. However, smaller trees have also been shown to be sometimes less reactive than larger stems [7,58,61].…”
Section: Tree Growthsupporting
confidence: 93%
“…Nyyssönen (1954), Niemistö (1994) and Pukkala et al (1998) have argued earlier that both absolute and relative thinning responses in Scots pines (Pinus sylvestris), for example, are at their maximum among co-dominant and intermediate trees. In contrast, Jonsson (1974), Moore et al (1994), Hynynen (1995) and Pape (1999) have suggested the same relative thinning response irrespective of tree size, especially among trees that were dominant at the time of thinning.…”
Section: Introductionmentioning
confidence: 98%